Society explained an introduction - Rousseau, Nathan 1957- (Rowman & Littlefield, 2014)
"Introduces key concepts in sociology through engaging narrative examples. After an overview of the history of sociology, the book walks readers through subjects that include individualism; culture; socialization and imagination; values, money, and politics; marriage and family; religious diversity; and education and social change."--Publishers website.